If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(7-x)=0
We simplify the equation to the form, which is simple to understand
8(7-x)=0
Reorder the terms in parentheses
+(+56-8x)=0
Remove unnecessary parentheses
+56-8x=0
We move all terms containing x to the left and all other terms to the right.
-8x=0-56
We simplify left and right side of the equation.
-8x=-56
We divide both sides of the equation by -8 to get x.
x=7
| 11-(x+8)=8x-6 | | 9.75-p=64 | | 4x^4-18x^3+42x^2-108x+108= | | -13X+20=-11X | | V=1385n+18790 | | A^2=2209 | | 5x+4g=c | | 8=-3x+2(x-4) | | 6-2x=22 | | 4g+7=4g-1 | | 4(2x+1)-3(y+1)= | | -2=-1.75+k | | 12r^2-75=0 | | -2=7+k/(-4) | | 4(w+3)=w- 15 | | X=3x+12 | | 40+400+1= | | 7(3-y)=-3x+4 | | 21x+6=17x-16 | | -d^2+18d-81=0 | | -13X+20=-11 | | (5x-20)=3x | | 7h-3h-6=6 | | 5(x-1)(x+4)(2x-3)=0 | | -2=-1.75k | | 25=5(9x-4) | | 2x-9=6x-13 | | -2(3)+5+5(3)= | | 6x-2=12x+1 | | 2x^3-3x-20=0 | | y-(-16)=-12 | | -18+30=-4(x+5) |